Characteristics of COPD in never-smokers and ever-smokers in the general population: results from the CanCOLD study. Issue 9 (5th June 2015) - Tan, W C; Sin, D D; Bourbeau, J; Hernandez, P; Chapman, K R; Cowie, R; FitzGerald, J M; Marciniuk, D D; Maltais, F; Buist, A S; Road, J; Hogg, J C; et al.
Abstract : Background: There is limited data on the risk factors and phenotypical characteristics associated with spirometrically confirmed COPD in never-smokers in the general population. Aims: To compare the characteristics associated with COPD by gender and by severity of airway obstruction in never-smokers and in ever-smokers. Method: We analysed the data from 5176 adults aged 40 years and older who participated in the initial cross-sectional phase of the population-based, prospective, multisite Canadian Cohort of Obstructive Lung Disease study. Never-smokers were defined as those with a lifetime exposure of <1/20 pack year. Logistic regressions were constructed to evaluate associations for 'mild' and 'moderate-severe' COPD defined by FEV1 /FVC <5th centile (lower limits of normal). Analyses were performed using SAS V.9.1 (SAS Institute, Cary, North Carolina, USA). Results: The prevalence of COPD (FEV1 /FVC<lower limits of normal) in never-smokers was 6.4%, constituting 27% of all COPD subjects. The common independent predictors of COPD in never-smokers and ever-smokers were older age, self reported asthma and lower education. In never-smokers a history of hospitalisation in childhood for respiratory illness was discriminative, while exposure to passive smoke and biomass fuel for heating were discriminative for women. COPD in never-smokers and ever-smokers was characterised by increased respiratory symptoms, 'respiratory exacerbation' events and increased residual volume/total lung capacity, but only smokers had reduced DLCO/Va and emphysema on chest CT scans. Conclusions: The study confirmed the substantial burden of COPD among never-smokers, defined the common and gender-specific risk factors for COPD in never-smokers and provided early insight into potential phenotypical differences in COPD between lifelong never-smokers and ever-smokers. Trial registration number: NCT00920348 (ClinicalTrials.gov); study ID number: IRO-93326.